A randomised phase II study of azacitidine (AZA) alone or with Lenalidomide (LEN), Valproic acid (VPA) or Idarubicin (IDA) in higher‐Risk MDS or low blast AML: GFM's "pick a winner" trial, with the impact of somatic mutations. (19th April 2022) - Adès, Lionel; Duployez, Nicolas; Guerci‐Bresler, Agnes; Laribi, Kamel; Peterlin, Pierre; Vey, Norbert; Thepot, Sylvain; Wickenhauser, Stefan; Zerazhi, Hacene; Stamatoullas, Aspassia; Wattel, Eric; Recher, Christian; et al.
Abstract: In order to improve the outcome observed with azacitidine (AZA) in higher‐risk Myelodysplastic syndrome (MDS), its combination with other drugs in MDS must be evaluated. So far, no combination has not been shown to be more effective than AZA alone. AZA‐PLUS was a phase II trial that, in a "pick a winner" approach, randomly assigned patients with higher‐risk MDS, CMML and low blast count AML to: AZA; AZA plus lenalidomide; AZA plus Valproic Acid or AZA plus Idarubicin. 322 patients were included. After six cycles, 69 (21.4%) CR + PR were observed with no benefit from any combination. Median EFS and OS were 17.2 and 19.7 months in the whole cohort, respectively, with no difference across randomised arms. Infection and rates of hospitalisation during the first six cycles were higher in the AZA‐LEN And AZA‐IDA arm, related to increased myelosuppression. Factors associated with better response were IPSS, favourable or intermediate karyotype, haemoglobin, lower circulating blast count, fibrinogen level and lower LDH, while poorer survival was seen in therapy‐related MDS and, in the case of TP53, PTPN11 or CSF3R mutation. The combinations used did not improve the outcome obtained with AZA alone. However, our "pick a winner" randomised strategy may remain useful with potentially more active drugs to be tested in combination with AZA.